2017
DOI: 10.1016/j.clinthera.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immediate Administration of Antibiotics in Patients With Sepsis in Tertiary Care: A Systematic Review and Meta-analysis

Abstract: Immediate antibiotic administration (<1 hour) seemed to reduce patient mortality. There was some minor negative asymmetry suggesting that the evidence may be biased toward the direction of effect. Nevertheless, this study provides strong evidence for early, comprehensive, sepsis management in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
0
38
0
2
Order By: Relevance
“…4 Surviving Sepsis Campaign guidelines promote that antibiotics should be administered within 1 hour from sepsis recognition, since delay in antibiotic administration is associated with increased morbidity and mortality, 3,4 although the exact timing of antibiotic administration is still debated. [6][7][8] Sterling et al found no significant survival benefit if antibiotics were administered within 3 hours of ED triage or within 1 hour of shock recognition, 7 while Johnston et al suggested that antibiotic administration in septic patients within 1 hour reduced mortality. 6 Apart from timing of antibiotic administration, its appropriateness is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Surviving Sepsis Campaign guidelines promote that antibiotics should be administered within 1 hour from sepsis recognition, since delay in antibiotic administration is associated with increased morbidity and mortality, 3,4 although the exact timing of antibiotic administration is still debated. [6][7][8] Sterling et al found no significant survival benefit if antibiotics were administered within 3 hours of ED triage or within 1 hour of shock recognition, 7 while Johnston et al suggested that antibiotic administration in septic patients within 1 hour reduced mortality. 6 Apart from timing of antibiotic administration, its appropriateness is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Sterling et al found no significant survival benefit if antibiotics were administered within 3 hours of ED triage or within 1 hour of shock recognition, 7 while Johnston et al suggested that antibiotic administration in septic patients within 1 hour reduced mortality. 6 Apart from timing of antibiotic administration, its appropriateness is of utmost importance. In the present study, 91.8% received an appropriate empiric antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No association between time to antibiotic and outcome was found in other studies of patients with sepsis in the ED, bacteraemia and neutropaenia . Results of systematic reviews of observational studies have been inconsistent . In a recent large randomised controlled trial (RCT) investigating efficacy of pre‐hospital antibiotics for patients with infection, antibiotic therapy (ceftriaxone) was administered 96 min earlier in the intervention arm (26 min before triage compared to 70 min after) without mortality benefit (8% at 28 days in both groups) .…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Interestingly, a second systematic review and meta-analysis of patients with sepsis showed a significant 33% reduction in mortality odds when antibiotics were administered within 1 hour compared with more than 1 hour. 55 The statistical methods used in these two studies were different as were the methods of selection of the articles. Globally, all these data support the recommendations of the surviving sepsis campaign for an early administration of the antibiotics in sepsis and septic shock.…”
Section: Human Datamentioning
confidence: 99%